A comparative analysis of the complete chloroplast genome sequences of four peanut botanical varieties - Wang,Juan; Li,Chunjuan; Yan,Caixia; Zhao,Xiaobo; Shan,Shihua (PeerJ, 2018)
Background Arachis hypogaea L. is an economically important oilseed crop worldwide comprising six botanical varieties. In this work, we characterized the chloroplast (cp) genome sequences of the four widely distributed peanut varieties. Methods The cp genome data of these four botanical varieties (var. hypogaea, var. hirsuta, var. fastigiata, and var. vulgaris) were obtained by next-generation sequencing. These high-throughput sequencing reads were then assembled, annotated, and comparatively analyzed. Results The total cp genome lengths of the studied A. hypogaea varieties were 156,354 bp (var. hypogaea), 156,878 bp (var. hirsuta), 156,718 bp (var. fastigiata), and 156,399 bp (var. vulgaris). Comparative analysis of theses cp genome sequences revealed that their gene content, gene order, and GC content were highly conserved, with only a total of 46 single nucleotide polymorphisms and 26 insertions/deletions identified. Most of the variations were restricted to non-coding sequences, especially, the trnI-GAU intron region was detected to be highly variable and will be useful for future evolutionary studies. Discussion The four cp genome sequences acquired here will provide valuable genetic resources for distinguishing A. hypogaea botanical varieties and determining their evolutionary relationship.
Keywords: Arachis hypogaea; Comparative cp genomes; Genetic structure; Genetic variation